TFP5-Mediated CDK5 Activity Inhibition Improves Diabetic Nephropathy via NGF/Sirt1 Regulating Axis - Cao, Shi-Lu; Luo, Hong-Yan; Gao, Yong-Cai; Lan, Xiao-Mei; Liu, Shun-Yao; Li, Bo; Bao, Li; E., Jing; Ma, Danna; Zhang, Guo-Qing; Yang, Li-Rong; Bao, Xi; et al. (Frontiers in Cell and Developmental Biology, 2022)
Diabetic nephropathy (DN) is one of the leading causes of chronic kidney disease (CKD), during which hyperglycemia composed of the major force for the deterioration to end-stage renal disease (ESRD). However, the underlying mechanism triggering the effect of hyperglycemia on DN is not very clear and the clinically available drug for hyperglycemia induced DN is urgent to be developed. Here, we found that high glucose (HG) increased the activity of cyclin-dependent kinase 5 (CDK5) dependent on P35/25 and upregulated the oxidative stress and apoptosis of mouse podocytes (MPC-5). TFP5, a 25 amino acid peptide that inhibiting CDK5 activity, decreased the secretion of inflammation cytokines in serum and kidney and effectively protected the kidney function in db/db mouse from hyperglycemia induced kidney injuries. In addition, TFP5 treatment decreased HG induced oxidative stress and cell apoptosis in MPC-5 cells and kidney tissue of db/db mouse. The primary component analysis (PCA) of mRNAseq data showed that MPC-5 cell cultured under HG well discriminated from that under Low glucose (LG) conditions, indicating the profound influence of HG on the properties of MPC-5 cells. Furthermore, we found that HG significantly decreased the level of NGF and Sirt1, both of which correlated with CDK5 activity. Furthermore, knockdown of NGF was correlated with the decreased expression of Sirt1 while NGF overexpression leads to upregulated Sirt1 and decreased oxidative stress and apoptosis in MPC-5 cells, indicating the positive regulation between NGF and Sirt1 in podocytes. Finally, we found that K252a, an inhibitor of NGF, treatment could undermine the protective role of TFP5 on hyperglycemia induced DN in db/db mouse model. In conclusion, the CDK5-NGF/Sirt1 regulating axis may be the novel pathway to prevent DN progression and TFP5 may be a promising compound to improved hyperglycemia induced DN.